The triad of nesidioblastosis, congenital neuroblastoma and glomerulocystic disease of the newborn: a case report - Bulun, Almila; Sarici, S Umit; Soyer, Ozge Uysal; Tekşam, Ozlem; Yurdakök, Murat; Cağlar, Melda (The Turkish Journal of Pediatrics, 2005)
Neuroblastoma is the most common malignant tumor of the newborn, comprising 20% of all malignancies encountered during the neonatal period. We herein report a newborn who was born after 29 weeks’ gestation and died unexpectedly at the 12th hour of life with no response to vigorous cardiopulmonary resuscitation. Autopsy findings revealed a right pararenal mass; microscopic examination showed neuroblastoma. Although the pancreas was grossly normal, its microscopic sections revealed a reduced number of islets of Langerhans and dispersion of the islet cells throughout the exocrine cells of the pancreas, and immunocytochemistry for the pancreatic hormones confirmed the dispersion of the islet cells. Final pathologic interpretation thus concluded the presence of nesidioblastosis. Furthermore, microscopic examination of the kidney showed glomerulocystic disease. Although the association of congenital neuroblastoma and nesidioblastosis has recently been defined as a new complex, neurocristopathy, the triad of congenital neuroblastoma, nesidioblastosis and glomerulocystic disease of the newborn has not been reported previously. To our knowledge, our case is the first reported newborn presenting with this triad. In conclusion, the association of nesidioblastosis and/or renal glomerulocystic disease should be kept in mind when encountering a case of congenital neuroblastoma. However, whether the presence of glomerulocystic disease in association with those other neurocristopathic pathologies is a coincidental finding or shares a common pathophysiological mechanism remains to be determined.